2020
DOI: 10.18280/ti-ijes.642-431
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer from Two Spheroids in Tandem to a Power Law Fluid by Forced and Mixed Convection Modes

Abstract: A numerical study is carried out on convective heat transfer from an unconfined and stationary tandem of two spheroids to the surrounding flowing power law fluid of constant physical properties. Two modes of convection viz., forced convection and mixed convection are considered for the present study. The surface of both the spheroids is maintained at constant temperature. The focus of the investigation is to obtain the effect of pertinent variables (Reynolds number, Prandtl number, Richardson number, aspect ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The calculated data were the percent weight losses. Earlier studies on extraction of phenols from phenol fraction employing single stage washing with the alkali by Aruna Kumari 1 showed that the yield of crude phenol increased with increase in the strength of NaOH. The gas chromatogram (shown in Figure 2) for phenol fraction procured from 'Visakhapatnam Steel Plant, Visakhapatnam' gives the analysis for its constituent components as: Phenol 11.2 g.; ortho cresol 4.48 g; Meta & Para Cresol 6.05 g; Naphthalene 14.24 g and xylenol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated data were the percent weight losses. Earlier studies on extraction of phenols from phenol fraction employing single stage washing with the alkali by Aruna Kumari 1 showed that the yield of crude phenol increased with increase in the strength of NaOH. The gas chromatogram (shown in Figure 2) for phenol fraction procured from 'Visakhapatnam Steel Plant, Visakhapatnam' gives the analysis for its constituent components as: Phenol 11.2 g.; ortho cresol 4.48 g; Meta & Para Cresol 6.05 g; Naphthalene 14.24 g and xylenol.…”
Section: Resultsmentioning
confidence: 99%
“…In the current scenario, efficient energy usage and recovery of minerals and useful substances from effluents are highly essential [1,2]. Hence, the present study is envisaged to obtain the augmentation levels of improvements in the yield of phenols from phenol fraction, a coke oven by-product using two-stage alkali treatment and optimizing the yield of phenols with respect to the concentration (strength) of the alkali and the ratios of alkali solution used in both the stages.…”
Section: Introductionmentioning
confidence: 99%